2020
DOI: 10.7717/peerj.8731
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of HELLS (Helicase, Lymphoid-Specific) and ICAM1 (Intercellular adhesion molecule 1) as potential diagnostic biomarkers of lung cancer

Abstract: Although lung cancer is one of the greatest threats to human health, its signaling pathway and related genes are still unknown. This study integrates data from three groups of people to study potential key candidate genes and pathways related to lung cancer. Expression profiles (GSE18842, GSE19188 and GSE27262), including 162 tumor tissue and 135 adjacent normal lung tissue samples, were integrated and analyzed. Differentially expressed genes (DEGs) and candidate genes were identified, their expression pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…As to the outcomes, some recent studies showed that low miR-365a-3p correlated with poorer survival time ( 16 , 33 , 34 ). On the contrary, there are several evidences that high HELLS expression correlated with poorer prognosis ( 23 , 39 , 40 ). The contrary impact of miR-365a-3p and HELLS in cancer outcomes provides an in immediate evidence to support the anti-cancer function of miR-365a-3p in GC.…”
Section: Discussionmentioning
confidence: 99%
“…As to the outcomes, some recent studies showed that low miR-365a-3p correlated with poorer survival time ( 16 , 33 , 34 ). On the contrary, there are several evidences that high HELLS expression correlated with poorer prognosis ( 23 , 39 , 40 ). The contrary impact of miR-365a-3p and HELLS in cancer outcomes provides an in immediate evidence to support the anti-cancer function of miR-365a-3p in GC.…”
Section: Discussionmentioning
confidence: 99%
“…found that HELLS levels are increased in lung cancer. Overexpression of HELLS is correlated with the prognosis of lung cancer, indicating that HELLS may be a potential diagnostic biomarker for lung cancer ( 22 ). In the present study, we found that HELLS expression was upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma, HELLS is involved in chromatin remodeling and epigenetic silencing, thus promoting tumor proliferation and metastasis ( 48 ). Additionally, Zhu ( 49 ) found that high expression of HELLS was related to an improved prognosis in lung cancer patients. Xing ( 50 ) reported that HELLS expression levels were correlated with the OS of cervical carcinoma and endocervical adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%